Le rapport entre sagesse et piété dans l'Euthyphron de Platon - Remida, Aimen (Diakrisis, 2025)
In this paper, we examine the relation between the notions of wisdom and holiness on the basis of Plato's Euthyphro. In their attempts to define holiness, both interlocutors, Socrates and Euthyphro, demonstrate the existence of two different modes of thought, which reveals a kind of opposition between the philosophical perspective and the perspective of traditional theology. The analysis of key moments of the dialogue shows that real wisdom can only be a philosophical wisdom that is able to develop a philosophical conception of holiness. According to Socrates, this conception rests upon two pillars: a notion of virtue related to true knowledge, and a notion of the divine without any anthropomorphism. On the contrary, the alleged theological wisdom of Euthyphro, which refers to the religion of the Greeks, is nothing but a pseudo-wisdom that relies on the authority of the tradition and hence generates the dependence of both virtue and holiness on the anthropomorphic conceptions of the divine.